2017
DOI: 10.1161/atvbaha.117.309002
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps Drive Endothelial-to-Mesenchymal Transition

Abstract: Objective— An excessive release and impaired degradation of neutrophil extracellular traps (NETs) leads to the continuous exposure of NETs to the endothelium in a variety of hematologic and autoimmune disorders, including lupus nephritis. This study aims to unravel the mechanisms through which NETs jeopardize vascular integrity. Approach and Results— Microvascular and macrovascular endothelial cells were exposed to NETs, and subsequent effects on endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
165
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(182 citation statements)
references
References 54 publications
11
165
1
5
Order By: Relevance
“…Insufficient regulation of NE activity by A1AT importantly contributes to endothelial damage during acute lung injury (36) and nephritis (37) and also promotes tumor progression (38). Although A1AT is able to inhibit both NE released to the pericellular space and membranebound NE (39), restricted accessibility of plugged or condensed areas might lower the capacity of inhibition (40) and limit the efficacy of NE inhibition as a therapy for conditions such as cystic fibrosis (41).…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient regulation of NE activity by A1AT importantly contributes to endothelial damage during acute lung injury (36) and nephritis (37) and also promotes tumor progression (38). Although A1AT is able to inhibit both NE released to the pericellular space and membranebound NE (39), restricted accessibility of plugged or condensed areas might lower the capacity of inhibition (40) and limit the efficacy of NE inhibition as a therapy for conditions such as cystic fibrosis (41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, subclinical kidney injury may readily be missed until consecutive exposures to UV light compound the effects. While we found that neutrophil-mediated kidney inflammation in response to UV light does not cause clinical disease in healthy mice, such a mechanism may contribute to LN flares in photosensitive lupus patients in multiple ways: Fc receptor engagement by immune complexes could enhance neutrophil recruitment resulting in ROS and protease release 105,106 ; the heightened capacity of lupus neutrophils and LDGs to produce NETs, which in SLE patients are not cleared efficiently 107,108 , could lead to release of tissue-damaging proteases 109,110 , propagation of the IFN-I response 85,86 , or direct damage to the kidney endothelium by creating vascular damage and leakage 14,111 . Moreover, the underlying differences in lupus skin, such as enhanced IFN-I signaling 7,112,113 and defects in protective Langerhans cell population 114 could inform the extent and nature of neutrophil-mediated systemic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Underlining the role of endothelium in thrombus resolution, during the process of angiophagy, the endothelium engulfs clots up to a certain size, as demonstrated in an elegant study by Lam et al [131]. Similarly, endothelial cells have been recently shown capable of phagocytosing NETs to a certain extent [132].…”
Section: Clearance Hand In Hand? Degradation Of Fibrin and Netsmentioning
confidence: 97%